THE IMPACT OF EXISTENTIAL FACTORS ON PARENTAL SELF-EFFICACY IN SELF-HELP GROUP. AN INTERVENTION PROGRAM FOR PARENTS OF CHILDREN WITH ADHD - MELINA HAYOUN; CRISTIAN STAN (Studia Universitatis Babes-Bolyai, 2019)
ABSTRACT. Several studies indicate a number of aspects concerning the relationship between parents and their children diagnosed with ADHD. This relationship is characterized by frequent and ongoing conflict and tension in their daily interactions. This article presents findings that emerged from a research that examined an original intervention program that led a parent's guidance group based on Yalom's (1995) group therapy approach. The aim of the intervention program was to elevate the participants' parental self-efficacy in order to improve the relationship between their ADHD children on the daily conduction, and to instill management tools. The intervention program consisted of five factors from Yalom's list of therapeutic factors. These factors according to Yalom (1995) exist predominantly in a group constellation. For this research, three dimensions of parental self-efficacy were chosen: self-trust, containment and communication. Qualitative data were collected and analyzed in the light of these dimensions. Twenty persons participated in the intervention program, i.e., five fathers and 15 mothers of children having ADHD symptoms. The intervention program consisted of nine meetings held once a week for about an hour and a half. Five interviews were conducted before the beginning of the intervention, and five post-experimental interviews were conducted as well. Findings reveal an improvement in the parents' attitude toward their ADHD children by using efficiently the behavioral tools they obtained in the intervention program. The improvement is expressed by an increased containment ability, better communication and an increase of parental self-trust. These are the components of Parental Self-Efficacy (PSE) on which the research focused.